IT-Based Financial Management and Governance Training Role Toward Village Government Employee Understanding on Financial Management - Pratolo, Suryo; Jatmiko, Bambang (E-Jurnal Akuntansi, 2020)
This research aims to test the information technology-based financial management and governance of village government to optimize the village financial management in local government of Indragiri. The research method is done by giving survey questionnaires to 100 of village government employees. A paired sample t-test is used to test the capability of the employees in managing the financial before and after the training. The result shows that there is an increase in capacity in financial management and governance by all the village government employees. The theoretical maximum score from the respondents is 50, and the minimum is 10, so the average score is 30. Based on the data above, before the training, the employee’s understanding scores are below the average score, i.e., 24, 15. After the training, the employee’s understanding increases above the average score, i.e. 38, 77. Keywords: Village Government Employees; Training; Financial Governance.